Application of Video Conference Media in Learning - Lestari, Neta Dian; Hadiwinarto, Hadiwinarto (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2022)
The problem in learning is the inaccuracy of educators or lecturers in using learning media, in fact some lecturers do not use learning media. Whereas the learning media is everything related to tools and facilities with the aim of conveying information or messages in a lesson and streamlining communication between educators and students. Video conferencing is a medium that can display moving images with the help of signals. The purpose of this study was to look into how video conferencing was used to assess student achievement. This research was conducted on students of the accounting training study program at the University of Palembang in the management accounting course. The descriptive analysis was adopted in this study. Observation and testing are the methods used to collect data. The results showed the success of the learning process with the use of video conferencing tools. With the application of video conferencing media, it encourages students to be more enthusiastic about learning and observe carefully the material being taught so that it can improve student learning outcomes well.